Inducible HIV-1 Reservoir Quantification: Clinical Relevance, Applications and Advancements of TILDA - Lungu, Cynthia; Banga, Riddhima; Gruters, Rob A.; Procopio, Francesco A. (Frontiers in Microbiology, 2021)
The presence of a stable HIV-1 reservoir persisting over time despite effective antiretroviral suppression therapy precludes a cure for HIV-1. Characterizing and quantifying this residual reservoir is considered an essential prerequisite to develop and validate curative strategies. However, a sensitive, reproducible, cost-effective, and easily executable test is still needed. The quantitative viral outgrowth assay (QVOA) is considered the gold standard approach to quantify the reservoir in HIV-1-infected patients on suppressive ART, but it has several limitations. An alternative method to quantify the viral reservoir following the reactivation of HIV-1 replication-competent provirus detects multiply-spliced tat/rev RNA (msRNA) molecules by real-time PCR (tat/rev induced limiting dilution assay [TILDA]). This article provides a perspective overview of the clinical relevance, various applications, recent advancements of TILDA, and how the assay has contributed to our understanding of the HIV-1 reservoir.